Appropriate sodium supplementation increases serum sodium levels in elite athletes which are maintained during extreme exercise - - Weatherall, L.; Jutley, R. S.; Blow, A.; Nanjaiah, P.; Voysey, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Exercise Associated Hyponatraemia (EAH) results from overhydration with low-sodium drinks or water in the face of high sweat losses. EAH causes problems ranging from poor coordination, confusion and muscle weakness to seizures and death. There is little evidence linking sweat sodium losses to EAH. As net sodium losses can vary 13-fold amongst athletes training in the same session, it is important to collate such evidence(1).This study evaluates whether sodium supplementation based on individual sweat sodium levels can protect against EAH during extreme exercise compared to water alone. Methods: Randomised crossover study comparing H2ProHydrate (500, 1000 or 1500 mg/l sodium) to Evian water (5mg/L sodium) in 7 elite male athletes. Pre-trial all underwent the Precision Hydration pilocarpine-induced sweat sodium analysis. Randomisation was to water or H2Pro allowing ad libitum drinking for 72 hrs pre-trial while maintaining standard diet. Cross-over was undertaken 2 weeks later. Athletes were subjected to extreme exercise consisting of maintaining 70% VO2 max in a climate chamber at 28C, 55% humidity for 60 min followed by a 15-min blinded performance time trial(TT). Ad libitum drinking was allowed throughout. End-points were baseline serum sodium sampling (pre-trial), post-chamber exposure and post-TT exposure and drink volumes. Results: Mean sweat sodium concentration was 1043mg/l (range 430-1640). One athlete failed to complete the trial on water due to nausea and dizziness and was therefore excluded. Mean serum sodium levels were higher in all athletes on H2Pro pre-trial, following the 60-min chamber exposure and following the TT. Baseline mean(mmol/l):H2Pro 141.2;water 138.5 Post-chamber mean(mmol/l):H2Pro 141.7;water 138.2 Post-TT mean(mmol/l):H2Pro 141.5;water 138.7 Analysis showed that `high sodium sweaters` (>1380 mg/L or 60 mmol/l,n=3) increased their serum sodium by the highest margin(138 mmol/l on water vs.142 mmol/l on H2Pro). The remaining group show a modest rise(139 mmol/l on water vs.141 mmol/l). Ave. volume of drink consumed: 1758 ml ( H2Pro), 1505 ml (water) Conclusion: Appropriate sodium preloading allows higher serum sodium levels which are maintained during extreme exercise. The greatest increases are seen in high sodium excretors who would typically have the highest sodium losses during exercise. Increased voluntary drinking of H2Pro indicates greater palatability which may help prevent hyponatraemia. The lower water intake compared to H2Pro could explain why serum sodium levels while on water did not decrease to dangerous levels. These findings have implications on understanding the onset of EAH.